Money and Banking in Medieval and Renaissance Venice Volume I: Coins and Moneys of Account / Volume 1 / Volume 1 - Lane, Frederic Chapin, 1900-1984.; Mueller, Reinhold C.; Project Muse.; Project Muse. (2019)
Frederic C. Lane and Reinhold C. Mueller, in the first volume of Money and Banking in Medieval and Renaissance Venice, discuss Venice's economic achievement in terms of the complex system the city's inhabitants developed to manage moneys of account and coins. Money merchants of Venice developed a system whereby a premium attached to moneys of account acted as a stabilizing force and allowed merchants to engage in long-term trade. This system, according to the authors, helped establish Venice as a dominant city-state in international trade and exchange. This book outlines the development and success of this system through 1508. At the time it was first published, this book made a significant contribution to the history of money and economics by underscoring the large role that Venice played in the economic history of the West and the ascendance of capitalism as a structuring force of society.
Part I. The Background -- Part II. Venice's Moneys, Bullion Market, and Mint.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No derivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Originally published as Johns Hopkins Press 1985.
Includes bibliographical references (pages 637-670) and index.
Description based on print version record.
Keywords: Money; Economic history; Banks and banking; Economic history -- 16th century; Banks and banking -- Italy -- Venice -- History; Money -- Italy -- Venice -- History; Italy -- Venice; Venice (Italy) -- Economic conditions; 1500-1599; Electronic books; History; Electronic books